MANAJEMEN PENDIDIKAN NON FORMAL DUSUN I DESA CIBADUNG - Matnur Ritonga; Nafa Lutfia; Agung Pandu; Reni Agustin; Febriza Putri; M. Daffa Akbar; Nur Fauzan; Asub Robbani (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2022)
The lack of social interaction between village youth and participation in existing community activities causes the potential of village youth to not develop, plus the lack of supervision from parents because the majority of the village community work as factory workers from morning to evening. Real Work Lecture (KKN) is a forum for students to learn and understand the characteristics of life in society, so that students can play a role and participate actively in society. The essence of this KKN is how students can learn and go directly to the field to help the community. Therefore, the KKN program indirectly gives full responsibility to KKN participants to provide services to the people of Cibadung Village and it is very beneficial for students, because researchers gain new knowledge and experience about how to socialize.